2011
DOI: 10.1007/s00240-011-0406-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of combined use of potassium citrate and tamsulosin in the management of uric acid distal ureteral calculi

Abstract: In this article, we investigated the effect of the combined use of tamsulosin and potassium citrate (Uralyt-U(®)) for the treatment of uric acid stones in the distal ureter. The study was designed as a prospective, double blind randomized controlled trial. A total of 191 adult patients with radiolucent distal ureteral calculi were recruited. We included patients with solitary stones ≥5 mm with mild or moderate hydronephrosis and a normal contralateral tract. The patients were randomized into four equal groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 24 publications
0
23
0
1
Order By: Relevance
“…145 In addition, the combination of alpha blockers (such as tamsulosin) and potassium citrate have been associated with significantly higher stone-free rates when compared with either therapy alone or with placebo in patients with distal ureteric UA stones (84.4%, 68.8%, 58.7%, and 26.1%, respectively). 146 Although UA stones are easy to fragment by SWL, they are difficult to localize due to their radiolucency. Contrast media injection, either through the intravenous route, retrograde ureteropyelography through a ureteral catheter, or antegrade administration through a nephrostomy tube, can be used to localize the radiolucent UA stones.…”
Section: Uric Acid Stonesmentioning
confidence: 99%
“…145 In addition, the combination of alpha blockers (such as tamsulosin) and potassium citrate have been associated with significantly higher stone-free rates when compared with either therapy alone or with placebo in patients with distal ureteric UA stones (84.4%, 68.8%, 58.7%, and 26.1%, respectively). 146 Although UA stones are easy to fragment by SWL, they are difficult to localize due to their radiolucency. Contrast media injection, either through the intravenous route, retrograde ureteropyelography through a ureteral catheter, or antegrade administration through a nephrostomy tube, can be used to localize the radiolucent UA stones.…”
Section: Uric Acid Stonesmentioning
confidence: 99%
“…El tamañ o medio de las litiasis osciló entre 2,9 29 y 7,9 mm 48 . Cuatro de los artículos incluidos especifican que má s del 60% de los pacientes presentaron litiasis mayores de 5 mm 14,34,36,48 .…”
Section: Caracterı´sticas De Los Estudios Incluidosunclassified
“…Two studies exclusively enrolled participants with a minimum stone size of 4 mm. 17,24 Large stone size definitions are listed in Figure 2. In the subgroup meta-analysis of large stone size, the I 2 statistic was 33.1% (P¼.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 8 placebo-controlled, double-blinded, randomized trials of tamsulosin in patients with ureteral stones, only 1 included ureteral stones of all locations, 8 whereas the remaining studies included distal ureteral stones identified by CT or kidney, ureter, and bladder radiographs. Four studies were conducted in an emergency department (ED) setting, 8,9,19,23 and 4 were conducted in urology clinics in a number of different countries, 17,18,21,24 including Australia, Egypt, France, India, Qatar, Switzerland, the United Kingdom, and the United States.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation